Impact of COVID-19 on Social Life: A Mental Health Emergency during Lockdown Period - Faisal Mahamude, Abu Shadate; Farhana, Kaniz (Future Science, 2025)
In December 2019, Wuhan, Hubei province, China, became the center of an outbreak of pneumonia, which later was discovered to be a new virus called the Coronavirus, leading to a pandemic. On April 13, 2020, the Coronavirus affected most of the world. It was expected to impact on the mental health of children during this pandemic. Social media, various forms of networks, and newspapers made it nearly impossible to escape the lockdown situation. That ongoing storm changed children's physical and mental situation, especially because their brains were working more on the internet to pass the pandemic time. To figure out the mental health condition of children during the pandemic, it was conducted to lockdown children for quantitative analysis. One of the respondents delivered his expression that he felt like he was in jail inside his home during that horrible lockdown period. Here, an online survey was conducted by a team of children, the respondents had a moderate level of knowledge of feedback on the question; therefore, the very initial primary output had been recorded. However, it needed to escalate to consciousness and address the change in those children's psychological activities within this lockdown period of COVID-19 (Coronavirus).